PENILAIAN KINERJA PERGURUAN TINGGI ISLAM DENGAN BALANCED SCORECARD AGAR TERWUJUD LEMBAGA PENDIDIKAN ISLAM BERBASIS MAQASID SYARIAH - Zuraidah, Zuraidah; Aisayah, Esy Nur (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
In improving organizational performance, alignment an organizations and individuals in the organization is very important. Balanced Scorecard is one of the alternative performance measure that aims to combine the performance measures of financial and non-financial. Inspired by Kaplan and Norton, the concept was developed in four perspectives: financial, customer, internal process and learning and growth. This article discusses how to build a balanced scorecard, include determining the strategic objectives, measures, targets, initiatives, and implementing the balanced scorecard in public organizations. The performance assessment of Islamic Universities have: 1) strategic targets financial perspective: the ability to obtain funding and cost efficiency, 2) strategic objectives perspectives of stakeholders, namely the satisfaction and pride for students, 3) strategic objectives of internal process perspective is a internal business portal, process and policy procedures, financial systems and reporting, internal control and performance measurement, research and community service quality, 4) strategic objectives of learning and growth perspectives improve the professionalism of human resources, improve the quality and infrastructure facilities. Islamic university has 21 strategic objectives in the four perspectives of the balanced scorecard. As well as the maqasid syariah used as an indicator both in aligning the results of an assessment of the performance of the Islamic universities.